Study on the Relationship between Different Body Mass Indexes and Puncture Pain and Image Quality in Patients Undergoing Coronary Angiography with Intravenous Indwelling Needle - Jiani Ding; Xiaoyu Chen (Emergency Medicine International)
Objective. To investigate the effect of different body mass indexes (BMIs) on patients’ puncture pain, puncture success rate, and image quality in coronary angiography (CAG) performed with an intravenous indwelling needle, and to provide a basis for selecting the appropriate intravenous indwelling needle for CAG in patients with different BMIs in an outpatient clinic. Method. In this study, 300 patients undergoing CTA at the department of radiology in the First Affiliated Hospital of Wenzhou Medical University from January to May 2021 were divided into group 1 (BMI 1 ≤ 18.5), group 2 (18.5 < BMI ≤ 24), and group 3 (BMI > 24) according to their BMI, with 100 cases in each group, and a 20 G intravenous indwelling needle was used in each group. The age, sex, height, and weight of each patient were recorded, and the primary puncture success rate, contrast leakage rate, injection success rate, pain perception, and subjective ratings of image quality and objective indicators were compared in patients with different BMI values. Results. There was no statistically significant difference between the age, gender, and heart rate of the patients in the three groups (P>0.05). There was no statistically significant difference between the primary puncture success rate, injection success rate, and contrast leakage rate of the three groups of patients (P>0.05). The pain scores of group 3 during contrast injection were significantly higher than those of the remaining two groups (P<0.05), while the differences between the pain scores of group 2 and group 1 during contrast injection were not statistically significant (P>0.05); the comparison of the pain scores of the three groups during puncture and during retention was not statistically significant (P>0.05). The differences between the subjective ratings of image quality and the objective indicators of the three groups were not statistically significant (P>0.05). Conclusion. The 20 G indwelling needle can basically meet the coronary angiography examination of patients with different body mass indexes, but patients with a BMI greater than 24 are recommended to use a larger diameter indwelling needle to reduce contrast leakage as well as to reduce patient pain and improve patient comfort.